Upaya fasilitas masyarakat terhadap pelatihan dan pentas seni tari dan lagu daerah bagi anak–anak sebagai upaya dalam Proses pengembangan budaya di Dusun Cilimus, Desa Mekarsari, Kecamatan Cimaung - AL-Mighwar, Muhammad; Isfahani, Jaisy Muhammad; Khalimatusyaadah, Khalimatusyaadah; Aqillah, Wafa Azmii (Universitas Pendidikan Indonesia (UPI), 2023)
This research aims to uncover the approach and outcomes of efforts to enhance traditional dance and music skills in children through education and training. Art is considered an integral part of human life, including in the development of children. Aside from having aesthetic value, art also has the potential to stimulate children's creativity. Art education for children is regarded as a foundational element of the national education process, aimed at developing potential in various aspects such as cognitive, linguistic, artistic, moral, religious, motoric, and socio-emotional domains. One way to stimulate motoric development in children is through learning dance art, which can influence both gross and fine motor development. However, motoric abilities depend on each child's level of maturity. The approach used in this research involves two main aspects: formal and non-formal education.